Expert consensus statement to guide research into evidence-based classifcation of athletes for Para-Taekwondo - A Delphi study - Jeong, H. S.; O`Sullivan, D. M.; Rus, P. R.; de Oca, A. R. M. (Journal of Men`s Health, 2021)
Background and Objective: The objective of this study was to investigate various issues surrounding participation in Para-Taekwondo Kyorugi (sparring), with the aim of focusing on future research initiatives to improve the classification system and safety for participation in Para-Taekwondo.